Are we there yet? Increasing use of cardioprotective antihyperglycemic agents in patients with T2D and CVD or CV risk in the United States. (2nd November 2022) - Mody, Reema; Meyers, Juliana; Yu, Maria; Davis, Keith; Levine, Joshua A.
Abstract: Objective: To report on the use of antihyperglycemic agents (AHAs) by age (i.e. <65, ≥65 years) in patients with type 2 diabetes (T2D) and cardiovascular disease (CVD) or cardiovascular risk (CV risk) factors in the United States. Methods: Patients with T2D and CVD (CVD cohort) or T2D and an additional CV risk factor without pre-existing CVD (CV risk cohort) were identified from 2015 to 2019 in a claims database. Patients were followed from their first observed CVD diagnosis or CV risk factor for each year they were continuously enrolled or until occurrence of a CVD diagnosis (CV risk cohort only). Classes of AHAs received were reported by year, cohort, and age group. Results: From 2015 to 2019, the percentage of patients <65 years on glucagon-like peptide-1 receptor agonists (GLP-1 RAs) increased (CVD: 9–17%, CV risk: 9–17%) and was approximately twice that of those ≥65 years (CVD: 4–8%, CV risk: 4–8%); the percentage of patients <65 years on sodium-glucose cotransporter-2 (SGLT2) inhibitors increased (CVD: 11–16%, CV risk: 11–17%) and was approximately triple that of those ≥65 years (CVD: 3–6%, CV risk: 4–7%). Conclusions: The use of GLP-1 RAs and SGLT2 inhibitors increased during the study period; however, most patients did not receive these medications. Patients aged ≥65 years were particularly disadvantaged.